Sistem Informasi Data Penduduk Kantor Kepala Desa Asam Jawa Berbasis Web - Tambak, Nurmin (Journal of Computer Science and Information System(JCoInS), 2021)
Writing this final project aims to assist in how to design an application program in realizing and creating a program that will be run. The information System needed by the Tamarind Village Head Office which provides convenience in processing population data based on mutations and conveying population data information quickly, accurately and integrated. The methodology used is UML( Unifield Modeling Language),the language used is PHP and the database used by MySQL. Information System Design Management of Village Population Data Case Study at the Asam Jawa Village Head Office produces a web-baed population data management information system that is able to simplify the process of managing villagers’ data based on mutations and accelerate the process of making reports and submitting reports.